THE EFFECTIVENESS OF THE TEAM GAMES TOURNAMENT (TGT) COOPERATIVE LEARNING MODEL ON LEARNING OUTCOMES OF STUDENTS IN SMA NEGERI 3 SALATIGA - Dwi Ratnasari; Okto Dwi Widyanto; Tri Widiarto; Destri Sambara Sitorus; Faresta , Rangga Alif (Jurnal Tatsqif, 2023)
This study aims to analyze the effectiveness of the Team Games Tournament (TGT) cooperative learning model on the learning outcomes of class X/phase E SMA Negeri 3 Salatiga in economics subjects. This research includes collaborative classroom action research with a sample of all students in class X5 consisting of 34 students using two research cycles. The flow in each cycle is planning, implementing, observing, and reflecting. This study uses a quantitative approach with research instruments in the form of pretest, posttest, student activity sheets, and self-assessment to see the effectiveness of the TGT model learning process on learning outcomes. The results showed that, in the cognitive domain, there was an increase in learning outcomes with an average score of 76 for the first cycle and 81 for the second cycle, while in the affective domain, there was an increase in attitude with an average value of 80% in cycle I and 82% in cycle 2. Moreover, student activity was obtained from self-assessment through a questionnaire with an average score of 68.24% in cycle I and 81.76% in cycle II.  Furthermore, the gain test result of 0.37926 is included in the medium category. It is suggested that the application of the TGT model can increase understanding and activeness in teaching and learning activities as well as for innovation and development through the application of the TGT model especially for teachers and for other researchers to develop a TGT model that is integrated with interactive media and technology.